Anesthetic management of a maned Wolf (Chrysocyon brachyurus) under critical condition for pelvic limb amputation - Justo, André Augusto [UNESP]; Garofalo, Natache Arouca [UNESP]; Neto, Francisco José Teixeira [UNESP]; Geraldini, Caroline Medeiros [UNESP]; Freirias, Cristianne Dantas [UNESP]; Gonçalves, Raphael Augusto Baldissera [UNESP] (Universidade Federal do Rio Grande do Sul, 2019)
Background: The maned wolf (Chrysocyon brachyurus) is the largest south american canid and deemed a near threatened species according to the International Union for Conservation of Nature (IUCN). Typically found in Brazilian Cerrado, it is often a victim of animal trappings and vehicular accidents, where it may get deeply injured or end up fractured, demanding orthopedic procedures. Even though maned wolves are similar to the domestic dog, little is described regarding general anesthesia and its complications for major procedures in ill patients in the scientific database. This case report describes a successful blood transfusion and anesthetic management of a critically ill C. brachyurus. Case: An adult female maned wolf was rescued after getting steel-jaw trapped. After chemical restraint with intramuscular (IM) ketamine (12 mg/kg), midazolam (0.3 mg/kg) and methadone (0.3 mg/kg), physical examination showed exposed bones to the distal end of the right hind limb, pronounced dehydration and moderate anemia and thrombocytopenia according to blood count. Radiographic images enlightened multiple right tarsus fractures. As the wound was highly infected, which made the osteosynthesis procedure impossible, it was decided to amputate the limb on the following day. Subcutaneous (SC) lactated Ringer's solution (250 mL), IM meloxicam (0.2 mg/kg) and IM enrofloxacin (10 mg/kg) were also administered at first. On the following day, after aforementioned chemical immobilization, anesthesia was induced with dose-effect intravenous (IV) propofol (2 mg/kg) until orotracheal intubation was possible, and general anesthesia was maintained with isoflurane diluted in oxygen. Lumbosacral epidural anesthesia was obtained with 0.5% bupivacaine (0.25 mL/kg) and morphine (0.1 mg/kg) to provide analgesia and to reduce inhalant agent requirement. During surgery, hypotension was unresponsive to IV fluid challenges (5 mL/kg of third generation hydroxyethyl starch solution [6% tetrastarch] twice and 10 mL/kg of lactated Ringer's solution, both over 15 minutes) and enduring blood loss led to life-threatening hypovolemic anemia. Dopamine (7.5-12.5 µg/kg/min) and norepinephrine (0.1-0.6 µg/kg/min) IV infusions were not able to fully restore blood pressure, thus whole blood transfusion (300 mL) was carried out after blood collection from a healthy maned wolf. Several premature ventricular contractions (PVC) that promptly evolved to sustained ventricular tachycardia (VT) were observed and treated with 2% lidocaine (bolus of 2 mg/kg followed by constant rate infusion set at 50 µg/kg/ min). By extubation, electrocardiogram displayed sparse PVC and normotension could be achieved. Discussion: Even though there was no cardiovascular instability by the time epidural anesthesia was carried out, the latter could have contributed to the hypotensive crisis (mean arterial pressure < 40 mmHg) observed during general anesthesia. The decreasing MAP was also probably influenced by intense blood loss and previous dehydration and hypovolemia, as packed cell volume (PCV) dropped to as low as 15% during transanesthetic period. As whole-blood transfusion might be accompanied by adverse effects, it is usually held back as long as oxygen delivery is not compromised. However, the declining MAP, fluid therapy-related hemodilution, and an actual PCV potentially lower owing to dehydration led to blood transfusion. The procedure was not ideally approached as no blood type and cross-match were previously performed, although no other feasible options were available. Besides, tachyarrhythmias are known to increase oxygen consumption, so that VT could have resulted in negative cardiovascular consequences (including cardiac arrest). Since it is a vulnerable animal, this report may aid recognize and treat clinical conditions for the purpose of preservation of the species.
Manejo anestésico de um lobo-guará (Chrysocyon brachyurus) criticamente enfermo para amputação de membro pélvico
Keywords: Blood transfusion; Epidural; General anesthesia; Maned Wolf; Wild animals